Pharmacologic Activities¬ of 3’-Hydroxypterostilbene: Cytotoxic, Anti-Oxidant, Anti-Adipogenic, Anti-Inflammatory, Histone Deacetylase and Sirtuin 1 Inhibitory Activity - Jody K Takemoto; Connie M. Remsberg; Neal M. Davies (Journal of Pharmacy & Pharmaceutical Sciences, 2015)
Purpose: Delineate the selected pharmacodynamics of a naturally occurring stilbene 3’-Hydroxypterostilbene. Objective: Characterize for the first time the pharmacodynamics bioactivity in several in-vitro assays with relevant roles in heart disease, inflammation, cancer, and diabetes etiology and pathophysiology. Methods: 3’-Hydroxypterostilbene was studied in in-vitro assays to identify possible bioactivity. Results: 3’-Hydroxypterostilbene demonstrated anti-oxidant, anti-inflammatory, cytotoxic, anti-adipogenic, histone deacetylase, and sirtuin-1 inhibitory activity. Conclusions: The importance of understanding individual stilbene pharmacologic activities were delineated.  Small changes in chemical structure of stilbene compounds result in significant pharmacodynamic differences.